Cephalic Index among medical students of Tripura studying in Tripura Medical College. (Journal of Forensic Medicine & Toxicology, 2025)
The cephalic index is a crucial anthropometric measurement used to classify head shapes and assess race in various pop ulations. It has broad applications in forensic anthropology, clinical craniofacial analysis, and anthropological research.  This study aimed to determine the mean cephalic index among undergraduate medical students of Tripura Medical  College who are permanent residents of Tripura, and to analyse differences based on gender and ethnicity. A total of  323 students participated, including 175 females and 148 males. Standard anthropometric tools were used to measure  skull length and breadth, and the cephalic index was calculated as the ratio of maximum cranial breadth to maximum  cranial length multiplied by 100. The mean cephalic index observed was 80.87 ± 3.49, indicating a predominance of the  brachycephalic type (65%), followed by Mesocephalic (30%) and dolichocephalic (5%) skulls. Although females showed  a slightly higher mean cephalic index (81.05 ± 3.48) compared to males (80.65 ± 3.50), the difference was not statistically  significant (p = 0.315). However, a significant difference was found between ethnic groups, with non-Bengali students  showing a higher mean cephalic index (81.75 ± 2.85) compared to Bengali students (80.44 ± 3.70) (p = 0.001). These  results suggest that ethnicity plays a notable role in cranial morphology, whereas gender does not significantly influence  cephalic index. The findings provide valuable regional data for forensic and clinical applications and contribute to the  anthropometric profiling of populations in Northeast India.
Keywords: Cephalic index; Race; Brachycephalic; Mesocephalic; Dolichocephalic; Anthropometry; Ethnicity; Tripura